(untitled) (Zaporizhzhia Historical Review, 2021)
In the article the morally-valued priorities of young people of XIХ – beginning ХХth centuries are analysed; social and psychological terms of life of natives from a spiritual estate – pupils of spiritual academies, seminaries and Kyiv spiritual academy – for whom the process of social modernization was accompanied not only with breaking of the traditional mode but also with transformation of the world view of both parishioners and themselves are lit up in the article.